Epidemiology of measles in Southwest Nigeria: an analysis of measles case-based surveillance data from 2007 to 2012 (2014)
Background: In Nigeria, a system of measles case-based surveillance with laboratory confirmation of suspected cases was introduced in 2005 as one of the strategies for the control of measles morbidity and mortality. In this report, we provide an epidemiological distribution of confirmed cases of measles reported from the southwest of the country between 2007 and 2012, and predict the expected number of cases for the ensuing years. Methods: A descriptive analysis of persons and place and time of confirmed measles cases (laboratory and epidemiological link) reported in the case-based surveillance data was carried out. Using an additive time series model, we predicted the expected number of cases to the year 2015, assuming that current interventional efforts were sustained. Results: From the 10 187 suspected cases investigated during the time period, 1631 (16.0%) cases of measles were confirmed. The annual incidence rose from 1 case per million in 2007 to 23 cases per million in 2011. Cases were confirmed from all six states within the zone and most (97.4%) were in individuals aged less than 20 years. Seasonal variation existed with peaks of infection in the first and second quarters of the year. There was an increasing trend in the number of expected cases based on projections. Conclusions: Case-based surveillance provided an insight into understanding the epidemiology of measles infection in Southwest Nigeria. There is a need to work out alternate strategies for control of measles and to strengthen the surveillance system.